Implementasi E-learning di Pendidikan Kedokteran: Permasalahan pada Aspek Manusia, Organisasi, dan Teknologi - Tri Suwarno; Teduh Dirgahayu; Hendrik Hendrik (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
Merdeka Belajar Kampus Merdeka (MBKM) is one of the policies of the Minister of Education and Culture of the Republic of Indonesia. In this program, students are given the freedom to take courses outside the program of study so that they can achieve learning outcomes covering aspects of attitudes, knowledge, and skills optimally and always relevant. Association of Indonesian Medical Education Institutions (AIPKI) Region IV, through an online course program, opens elective block subjects for medical education of association members. Faculty of Medicine, Universitas Islam Indonesia (FM UII) as one of the members of the association, participated by implementing the e-learning system as a learning medium. However, the implementation of the e-learning system can still be improved in terms of benefits. This study aims to evaluate the e-learning information system in FK UII using the HOT-Fit method and provide recommendations for e-learning to have more benefits. Quantitative cross-sectional design research to measure the research variables of the HOT-Fit model, namely, Human (system use, user satisfaction), Organization (structure, environment), Technology (system quality, information quality, service quality), and Net benefits. The population in this study is a student participant of e-learning in FM UII with a sample size of 124 samples taken by random sampling. Data analysis was performed regression. Hypothesis testing showed that there were 13 accepted hypotheses and 4 rejected hypotheses. From this study, it can be concluded that the development of e-learning can still be needed to achieve more benefits obtained by learners by paying attention to user satisfaction, organizational support, and adequate technology.